Cannabidiol inhibits febrile seizure by modulating AMPA receptor kinetics through its interaction with the N-terminal domain of GluA1/GluA2. (November 2020) - Yu, Yongzhou; Yang, Zuxiao; Jin, Baohua; Qin, Xia; Zhu, Xiaoque; Sun, Jiahui; Huo, Lifang; Wang, Ri; Shi, Yongyun; Jia, Zhanfeng; Shi, Yun Stone; Chu, Shifeng; et al.
Graphical abstract: Highlights: Cannabidiol (CBD) significantly prolonged seizure latency and reduced seizure severity. CBD changed the amplitude of evoked EPSCs and inhibited the amplitude and frequency of miniature EPSCs. CBD lead to a faster deactivation in GluA1 and GluA2, and slower recovery in GluA1. CBD interacted with the N-terminal domain of GluA1 and GluA2. Abstract: Cannabidiol (CBD) is a major phytocannabinoid in Cannabis sativa. CBD is being increasingly reported as a clinical treatment for neurological diseases. Febrile seizure is one of the most common diseases in children with limited therapeutic options. We investigated possible therapeutic effects of CBD on febrile seizures and the underlying mechanism. Use of a hyperthermia-induced seizures model revealed that CBD significantly prolonged seizure latency and reduced the severity of thermally-induced seizures. Hippocampal neuronal excitability was significantly decreased by CBD. Further, CBD significantly reduced the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor (AMPAR) mediated evoked excitatory postsynaptic currents (eEPSCs) and the amplitude and frequency of miniature EPSCs (mEPSCs). Furthermore, CBD significantly accelerated deactivation in GluA1 and GluA2 subunits. Interestingly, CBD slowed receptor recovery from desensitization of GluA1, but not GluA2. These effects on kinetics were even more prominent when AMPAR was co-expressed with γ-8, the high expression isoform 8 of transmembrane AMPAR regulated protein (TARPγ8) in the hippocampus. The inhibitory effects of CBD on AMPAR depended on its interaction with the distal N-terminal domain of GluA1/GluA2. CBD inhibited AMPAR activity and reduced hippocampal neuronal excitability, thereby improving the symptoms of febrile seizure in mice. The putative binding site of CBD in the N-terminal domain of GluA1/GluA2 may be a drug target for allosteric gating modulation of AMPAR.